Parijoto (Medinilla speciosa) extract as a natural dye alternative for peripheral blood smears: A comparative study with giemsa stain - Meida Trisna; Indanah Indanah; Yunita Rusidah; Arief Adi Saputro; Anisa Sholikhati; Sherly Nur Ekawati (Journal of Indonesian Medical Laboratory and Science, 2026)
Background: Peripheral blood smear staining is an essential hematological procedure used to evaluate blood cell morphology. The commonly used standard stain is Giemsa stain; however, its chemical components may pose potential risks to health and the environment. Therefore, safer natural alternatives are needed. Previous studies have reported that anthocyanin-containing plant extracts, such as Hibiscus sabdariffa, Tectona grandis, and Garcinia mangostana, can effectively stain blood cells. Medinilla speciosa (parijoto) also contains anthocyanins and has potential as a natural dye. Objective: This study aimed to evaluate the staining quality of peripheral blood smears using Medinilla speciosa extract at different concentrations and to compare the results with a 10% Giemsa stain control. Methods: This laboratory-based experimental study used a post-test only control group design. A total of 30 blood smears were stained using Medinilla speciosa extract at concentrations of 25%, 50%, and 70%, along with a 10% Giemsa stain control. The extract was prepared using maceration with pH adjustment to optimize anthocyanin stability. Staining quality was assessed based on color intensity, background clarity, and erythrocyte morphology using a semi-quantitative scoring system. Data were analyzed using the Kruskal–Wallis test and Mann–Whitney U test. Results: Increasing extract concentration was generally associated with improved staining quality. A significant difference among groups was observed (p = 0.002). Pairwise analysis showed that the 70% extract was not significantly different from the 10% Giemsa stain control (p = 0.321), while lower concentrations differed significantly. Conclusion: The 70% Medinilla speciosa extract showed the best performance among extract groups and demonstrated comparable staining quality in certain parameters. However, Giemsa stain remains the more consistent standard. Further optimization is required before routine application.